Photochemical Study of a Three‐Component Photocyclic Initiating System for Free Radical Photopolymerization: Implementing a Model for Digital Light Processing 3D Printing. Issue 11 (10th September 2019) - Metral, Boris; Bischoff, Adrien; Ley, Christian; Ibrahim, Ahmad; Allonas, Xavier
Abstract: Vat photopolymerization technologies are promising 3D printing techniques in the field of additive manufacturing, which requires high performance and affordable photoinitiating systems (PIS). In this paper, we introduce a complex PIS based on safranine as photosensitizer and two redox additives. The photocycling mechanism is explored via laser flash photolysis (LFP) and its reactivity is investigated through real‐time Fourier transform infrared spectroscopy (RT‐FTIR). A model which predicts with good accuracy the change in conversion with both time and light intensity is proposed. Cure depth experiments are conducted and the critical energy (Ec) and penetration depth (Dp) are established for the resin used. The relationship between these parameters and the corresponding RT‐FTIR results was highlighted through the role of the conversion at the gel point, allowing optimization of the formulation. Finally, high resolution complex pieces are printed with the resin, whose composition was tailored in accordance with our studies, demonstrating the viability of this PIS in digital light processing (DLP) 3D printing. Abstract : Keep it moving : A photocyclic initiating system was mechanistically studied and applied to vat photopolymerization for 3D printing. A model is proposed which allows the prediction of the Jacob's parameters from photopolymerization experiments.